Repeated courses of low‐dose 2 × 2 Gy radiation therapy in patients with indolent B‐cell non‐Hodgkin lymphomas. (6th April 2020) - Saleh, Khalil; Michot, Jean‐Marie; Schernberg, Antoine; Lazarovici, Julien; Chahine, Claude; Danu, Alina; Khalife‐Saleh, Nadine; Rossignol, Julien; Ghez, David; Martin, Valentine; Mazeron, Renaud; Fermé, Christophe; et al.
Abstract: Purpose: In patients with indolent B‐cell non‐Hodgkin's lymphoma (B‐NHL), one course of low‐dose radiotherapy (LD‐RT) 2 × 2 Gy is emerging as new option of therapy in palliative setting. Efficacy of LD‐RT when repeated remains to be determinate. This study aims to assess the efficacy of repeated LD‐RT given in patients with indolent B‐NHL. Materials and Methods: All consecutive adult patients who received two or more courses of LD‐RT 2 × 2 Gy for indolent B‐NHL at Gustave Roussy institution, during the period 1990‐2015 were retrospectively investigated. Results: Thirty‐three patients received two or more courses of LD‐RT for indolent B‐NHL during the study period. The median age was 57 (range 37‐80) years, histological types were distributed among follicular lymphoma (n = 24 pts; 73%), marginal‐zone lymphoma (n = 6 pts; 18%), and primary cutaneous follicle center lymphoma (n = 3 pts; 9%). The median number of low‐dose radiation therapy courses given per patients was 2 (range 2‐6). The overall response rates following the first and the second course of LD‐RT were 96% and 88%, respectively ( P  = .31). The 1‐ and 2‐years local control rates following the first courses of LD‐RT were 94% (CI 95: 86‐100) and 94% (CI 95: 86‐98); and were 91% (CI 95: 82‐100) and 88% (CI 95: 77‐100) following the second course of LD‐RT ( P  = .39). Conclusion: The repeated courses of LD‐RT offered similar efficacy compare with the first course in patients with indolent B‐NHL. LD‐RT repeated is a simple, easy to give, and non‐toxic asset that could be investigated as treatment option in patients with indolent B‐NHL. Abstract : Low dose radiotherapy is a valuable and non‐toxic treatment option in the form of indolent lymphoma. The effectiveness of low‐dose radiotherapy is similarly maintained when repeated once or even twice (RT1, RT2 and RT3).